The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11920-016-0664-7
|View full text |Cite
|
Sign up to set email alerts
|

Depression During Pregnancy and Postpartum

Abstract: Depression is a common complication of pregnancy and the postpartum period. There are multiple risk factors for peripartum mood disorders, most important of which is a prior history of depression. Both depression and antidepressant medications confer risk upon the infant. Maternal depression has been associated with preterm birth, low birth weight, fetal growth restriction, and postnatal cognitive and emotional complications. Antidepressant exposure has been associated with preterm birth, reductions in birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(148 citation statements)
references
References 110 publications
6
113
0
14
Order By: Relevance
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 51%
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 51%
“…Maternal stress also can simultaneously affect outcomes of the child by altering the functions of the maternal and fetus, leading to sleep disorder, increased risk of infl ammatory disease such as asthma [11,19]. These stressful events are closely related to psychological health, maternal-fetal relationship, and infant outcomes [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [4,19] support that pregnant women have more complications during the COVID-19 epidemic period than they had before the pandemic. Anxiety during pregnancy may be associated with many complications, such as preterm action [20,21], low birth weight, fetal growth restriction [21,22], and postnatal complications [23].…”
Section: Resultsmentioning
confidence: 99%